EASYCRYPT (automatic media encryption) - Tan, Caiyu. (2009)
With the importance of data security, organizations are paying more attention on the confidentiality of their data. Data can be carried around portably by the means of a portable storage device such as thumb drive. Given the small physical size of the storage devices, it could be a common problem where people will misplace or lost these devices. If the device contains any confidential data and these data falls into the hands of some unintended people, there could be serious implications. Be it intended or unintended, breach of data can be a serious issue. In the market, there are available products such as Drivecrypt, Folder Lock and etc. that provide the features of protecting the data stored in these portable storage devices. However, there are still some flaws in these products that can still be improved on. The program that runs on these portable storage devices must be efficient and lightweight. Most important of all, it must be easy and must not bring any inconvenience for the users. With all these in mind, I propose to create an automated media encryption program, which I name it as EASYCRYPT. This product will incorporate the basic features of the existing products and adds on new features such as secure on‐screen keypad, event logging and automatic encryption/decryption.